Deciphering Gas Dynamics and Star Formation in a z = 1.1 Main-sequence Spiral Galaxy with ALMA and JWST - Zhaoran Liu; Tadayuki Kodama; Takahiro Morishita; Kianhong Lee; Fengwu Sun; Mariko Kubo; Zheng Cai; Yunjing Wu; Zihao Li (The Astrophysical Journal)
We present a joint analysis of high-resolution CO(2–1) and Paschen- α (Pa α ) emission lines to trace gas dynamics and spatially resolved star formation in ASPECS-LP.3 mm.06, a z = 1.1 main-sequence galaxy. Utilizing data from the Atacama Large Millimeter/submillimeter Array and JWST NIRCam wide field slitless spectroscopy, we explore both ionized gas and molecular gas within this galaxy. With a substantial molecular gas fraction ( f _mol = 0.44  ±  0.02), ASPECS-LP.3 mm.06 remains on the star-forming main sequence and adheres to the Kennicutt–Schmidt relation, indicating typical gas-to-star conversion efficiency. Our analysis reveals extended structures across multiple wavelengths, suggesting regulated star formation within a stable disk. The spatially resolved star formation efficiency and kinematic analysis indicate that ASPECS-LP.3mm.06 features a smooth mass assembly process across the bulge and disk. Additionally, the galaxy exhibits modest dust extinction ( A _V = 0.8), potentially linked to self-regulation during bulge formation. These findings position ASPECS-LP.3mm.06 as a prototypical galaxy, offering valuable insights into the mechanisms governing normal disk galaxy growth at z ∼ 1.